Inclusive Education And The Primary School Teacher Education Curriculum In Zimbabwe: The Need For A Paradigm Shift - Jenjekwa, Vincent; Rutoro, Ester; Runyowa, Julius (Globeedu Group, 2022)
n line with global trends regarding people with disabilities, Zimbabwe swiftly promulgated policies to ensure the inclusion of previously marginalised pupils in schools. Though policies have been easy to craft, a major challenge remains in that the policies have not been translated into tangible transformational approaches in the primary school teacher education curriculum. Primary school education is a critical base which should unequivocally show commitment to inclusion in explicit and ostensible ways rather than through mere spoken or written pronouncements. This qualitative research established that because of the dearth of clear commitment in teacher education curriculum, the college products are largely ill equipped to deal with children with special learning needs. A serious discord between policy pronouncements and the primary teacher education curriculum exists. There is a need for a paradigm shift in the primary school teacher education curriculum for production of teachers who can effectively handle both mild and severe cases of special need failing which the dream for inclusivity will always remain a dream. The research is in the form of a case study of three primary school teacher training colleges in Masvingo province, Zimbabwe. Interviews with college administrators, teacher educators and student teachers alongside the observation of general infrastructure and routines at these colleges as well as analysis of relevant documents which include, among others, syllabi, schemes of work, lecture notes and even assignment and examination questions provided the data for analysis.